Preservation of the Historical Architectural Environment in a Modern City - A. Nikolaenko, Volodymyr; V. Nikolaenko, Volodymyr; Zubrichev, Oleksandr (International Journal of Engineering and Technology, 2018)
In the article the problem of preservation of monuments of architecture in the modern city is considered. Today, this is one of the main tasks of urban development, which is associated with a change in the filling of the architectural environment of the historical centers of the modern city. The experience in this area is generalized in order to reveal new principles that allow testing on the real material the interaction of structures of different epochs for understanding their reconstruction, preservation and protection. In the field of protection of architectural monuments, there is no necessary legal support, as well as guarantees of investments for maintaining and preserving the historical environment. The research was carried out, first of all, on examples of historical architectural objects of the city of Poltava, where, along with architectural monuments, construction of new buildings takes place, which in most cases do not correspond to the stylistic features of historical buildings and distort the urban historical environment, not taking into account the traditions and practice of building previous centuries.Â Â
Keywords: architecture; architectural monuments; modern city; preservation; reconstruction.